Massimo Banzi: Building Arduino. - Severance, Charles (Computer (00189162), 2014)
Massimo Banzi describes the origins and evolution of the Arduino microcontroller. The first Web extra at http://youtu.be/0VAbvQ2Ti50 is a video interview in which author Charles Severance speaks with Massimo Banzi about the origins and evolution of the Arduino microcontroller. The second Web extra at http://youtu.be/N6wN1_qLfEQ is an audio recording of author Charles Severance reading his Computing Conversations column, in which he discusses his interview with Massimo Banzi about the origins and evolution of the Arduino microcontroller.